Design and Kinematics Analysis of a 3-DOF Rigid Flexible Coupling Parallel Ankle Rehabilitation Mechanism - Zhiguang Ma; Kangkang Wang; Leile Zhang; Yan Song; Shaowei Jia (Jixie chuandong)
Based on the study of the ankle rehabilitation mechanism， a 3-DOF rigid flexible coupling parallel ankle rehabilitation mechanism is proposed， which solves the problems of poor compliance and large inertial impact existing in the present rehabilitation institutions. The forward and inverse kinematics solutions of the parallel rehabilitation mechanism are solved， and the correctness of the calculation results is verified. Furthermore， the Jacobian matrix of the mechanism is solved， the relationship between the rope speed change of the mechanism and the speed change of the moving platform is analyzed， and the position change and speed change of the mechanism are simulated and analyzed. The results show that the designed mechanism moves smoothly， can meet the requirements of ankle rehabilitation training， and also provides a theoretical basis for the research and development of the follow-up control system.